2007
DOI: 10.1557/proc-1017-dd01-10-ee01-10
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Catalysts For Si-Technology Compatible Growth Of Si Nanowires

Abstract: The use of Au nanoparticles as catalysts for growth of Si nanowires poses fundamental reliability concerns for applications in Si semiconductor technology. In this work we show that the choice of catalysts can be broadened when the need for catalytic precursor dissociation is eliminated. However, the requirements for selective deposition in a gas phase transport ñlimited regime become stringent. When competing deposition of amorphous Si can bury the particles faster than the incubation time for VLS growth, no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…7 The high resolution spectrum of In 3d (Fig. 4c) The key difference between this study and previous metal catalyst-free approaches is that Ge NW growth is uniquely 15 facilitated by the vapor phase of the organic solvent growth medium, with no material formation in solution.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…7 The high resolution spectrum of In 3d (Fig. 4c) The key difference between this study and previous metal catalyst-free approaches is that Ge NW growth is uniquely 15 facilitated by the vapor phase of the organic solvent growth medium, with no material formation in solution.…”
mentioning
confidence: 79%
“…4 While this route has been widely adopted in the controlled synthesis of NWs, its viability for device applications has been limited due to 35 inherent Au contamination of the resultant nanostructures, 5 prompting interest in the use of alternative metal catalysts. 6,7 Concurrently, the more recent discovery of routes to Ge NWs grown without metal catalyst particles deemed as 'unseeded' or 'self-seeded' processes offer even higher purity NW 40 formation. 8 Ge et al showed that anisotropic growth of crystalline Ge nanostructures was possible in organic solution.…”
mentioning
confidence: 99%
“…Thus the growth temperature has to be higher than the eutectic temperature of 577 o C so that the Al-Si catalyst particle is a liquid [21,24].…”
Section: Morphologymentioning
confidence: 99%
“…Iacopi et al [24] used 10 nm Al particles prepared via PVD method to grow SiNWs by the PECVD. They found that Si layer that covered the catalyst is amorphous.…”
Section: Crystalline Structurementioning
confidence: 99%
“…An alternative approach is represented by Plasma-Enhanced Chemical Vapor Deposition (PECVD), a powerful method allowing depositing semiconductor thin films from a gas phase precursor at sample temperatures lower than in CVD [14,15]. PECVD indeed proved successful for NW growth at a relatively fast rate often below the eutectic point of the different catalysts used (e.g., Au [14][15][16]; Al [17]; Ga or In [16][17][18]). However, PECVD leads to the formation of mixed amorphous/crystalline structures, making the separation of the deposition by-products from NWs difficult [19].…”
Section: Introductionmentioning
confidence: 99%